2017
DOI: 10.1007/s10916-017-0700-0
|View full text |Cite
|
Sign up to set email alerts
|

Cancelled Primary Care Appointments: A Prospective Cohort Study of Diabetic Patients

Abstract: Patients scheduled for primary care appointments often cancel or no show. For diabetic patients, nonattendance can affect continuity of care and result in higher emergency department (ED) and hospital use. Nonattendance also impacts appointment scheduling, patient access, and clinic work load. While no show has received significant attention, little research has addressed the prevalence and impact of appointment cancellation. Data on 46,710 appointments for 7586 adult diabetic patients was used to conduct a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Thirty‐four studies of varying designs were identified (15 observational, 1 randomized control trial, 9 qualitative, 5 surveys, 4 service improvements). Sixteen were studies from the UK , four from Europe , six from North America and eight from the rest of the world . Six studies specifically focused on young adults in transition from paediatric to adult services, each of which had a mean participant age of >18 years (age range 15–30 years) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty‐four studies of varying designs were identified (15 observational, 1 randomized control trial, 9 qualitative, 5 surveys, 4 service improvements). Sixteen were studies from the UK , four from Europe , six from North America and eight from the rest of the world . Six studies specifically focused on young adults in transition from paediatric to adult services, each of which had a mean participant age of >18 years (age range 15–30 years) .…”
Section: Resultsmentioning
confidence: 99%
“…Reported baseline non‐attendance rates at diabetes appointments were mostly between 10 and 30% , but the extreme ranges were 8.3 and 76% . The means of quantifying non‐attendance varied; some studies calculated the number of missed appointments as a percentage of total booked appointments .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the impact of a particular feature on no-show rates, several studies have been conducted using large datasets. McComb et al [20] find that the impact of lead time on no-show rates is greater among patients who cancel and were rescheduled. Ellis, Luther & Jenkins [21] conclude that reduced sleep consequence of the spring daylight savings change, increased no-show rates, suggesting seasonality on the patterns.…”
Section: Related Workmentioning
confidence: 99%